2019
DOI: 10.3389/fpsyg.2019.01561
|View full text |Cite
|
Sign up to set email alerts
|

“Telling me not to worry…” Hyperscanning and Neural Dynamics of Emotion Processing During Guided Imagery and Music

Abstract: To analyze how emotions and imagery are shared, processed and recognized in Guided Imagery and Music, we measured the brain activity of an experienced therapist (“Guide”) and client (“Traveler”) with dual-EEG in a real therapy session about potential death of family members. Synchronously with the EEG, the session was video-taped and then micro-analyzed. Four raters identified therapeutically important moments of interest (MOI) and no-interest (MONI) which were transcribed and annotated. Several indices of emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 82 publications
0
60
1
3
Order By: Relevance
“…Moreover, it has been suggested that hyperscanning has great potential for music therapy (Hunt, 2015). Fachner et al (2019) measured dual-EEG of an experienced therapist (“Guide”) and client (“Traveler”) in a real music therapy session, which was combined with audiovisual recordings. They identified and quantitatively investigated therapeutically important moments of interest (MOI) and no-interest (MONI).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been suggested that hyperscanning has great potential for music therapy (Hunt, 2015). Fachner et al (2019) measured dual-EEG of an experienced therapist (“Guide”) and client (“Traveler”) in a real music therapy session, which was combined with audiovisual recordings. They identified and quantitatively investigated therapeutically important moments of interest (MOI) and no-interest (MONI).…”
Section: Discussionmentioning
confidence: 99%
“…They identified and quantitatively investigated therapeutically important moments of interest (MOI) and no-interest (MONI). The authors suggested that combining dual-EEG (hyperscanning) with detailed audiovisual and qualitative data can provide pivotal information for further research into music therapy (Fachner et al, 2019). There is no doubt that registration of instrument-brain coupling would further improve this interesting and therapeutically significant approach.…”
Section: Discussionmentioning
confidence: 99%
“…However, HRV data represents a novel approach to measuring the experience of flow in musicians by means of physiological assessment. In the scientific literature, individual EEG recordings have been used in combination with video data to understand the emotional interplay involved in music therapy (Fachner et al, 2019), but there has been little research about flow and its mechanisms in interactive situations such as in performances by groups of musicians (Csikszentmihalyi, 1990;Sawyer, 2007;Hart and Di Blasi, 2015;Oláh, 2015, 2017).…”
Section: Flow and Heart Rate Variabilitymentioning
confidence: 99%
“…In addition to utilizing live entrainment music to ensure ecological validity, future research should investigate the degree to which these different music interventions utilize different neural networks, and how these networks are affected by variables such as pain and other medications, music and sound variables, and type of pain. To investigate the EEG of the intersubjective experience of interventions such as entrainment, researchers would need to involve the therapist’s brain activity in a hyperscanning investigation ( Hunt, 2015 ; Fachner et al, 2019 ). Such information is essential to understanding the mechanism of these greatly needed interventions to add effective, beneficial, and low-risk pain relief options to patients.…”
Section: Limitations and Conclusionmentioning
confidence: 99%